Larf - Spires, Ashley, 1978- (Kids Can Press, 2012)
"No one believes Larf exists, and he likes it that way. Larf, you see, is a sasquatch, the only sasquatch in the world (or so it seems). He has a very pleasant, and very private, life in the woods, where on any given day he might be found jogging, gardening or walking Eric, his pet bunny. But everything changes one morning when Larf discovers that another sasquatch is scheduled to make an appearance in the nearby city of Hunderfitz. What?! That must mean he's not the only sasquatch in the world! Excited by the prospect of having a friend to share hair grooming tips with (and let's face it, teeter-tottering alone is no fun), Larf disguises himself as a city slicker and heads for Hunderfitz -- where he's in for a couple enormous surprises."--Amazon.